PANDUAN PRAKTIS DIIT DAN KEGIATAN FISIK PASIEN DIABETES MELLITUS TIPE II - Ester Ronauli Sihotang, Ester (2021)
The purpose of making this product is as information material for patients with type 2 diabetes mellitus related to diet and physical activity so that they can control blood glucose levels regularly. Making the final product in the form of a booklet containing the concept of type 2 diabetes mellitus, the concept of eating patterns, the concept of physical activity and tips for healthy living. This booklet is intended for patients with type II diabetes mellitus as one of the reading materials designed to be interesting and easy to understand by readers. This booklet was created as a very important guide to be known by the public, especially in type II diabetes mellitus patients, in order to maintain a diet and physical activity lifestyle in the surrounding environment, so that one of the recommended sources for reading is a booklet which is considered the most effective. suitable as a guide in health education for the community.